Phylogenetic Analysis of ALV-J Associated with Immune Responses in Yellow Chicken Flocks in South China - Qihong Zhang; Guodong Mo; Tingting Xie; Zihao Zhang; Huali Fu; Ping Wei; Xiquan Zhang (Mediators of Inflammation)
The aim of this study was to better understand the sequence characteristics and immune responses in avian leukosis virus subgroup J (ALV-J) infected yellow chicken flocks in South China. We isolated four strains of ALV-J virus from these flocks, which were then identified by several methods, including subtype-specific polymerase chain reaction (PCR), enzyme-linked immunosorbent assay (ELISA), and immunofluorescence assay (IFA). All four viruses were sequenced for their complete genomes and named GD19GZ01, GD19GZ02, GD19GZ03, and GD19GZ04. In comparison with the reference sequence, the homology analysis showed that the gag and pol genes were relatively conserved, whereas env contained much variation. Both GD19GZ01 and GD19GZ02 almost entirely lacked the rTM region and E element, while the latter was retained in GD19GZ03 and GD19GZ04. Moreover, the virus replication levels in GD19GZ03 and GD19GZ04were much higher than those in GD19GZ01 and GD19GZ02. And three virus recombination events in GD19GZ01 and GD19GZ02 were revealed by the results of PDR5 and SimPlot software analysis. Additionally, we found that some interferon-stimulating genes (CH25H, MX, PKR, OAS, and ZAP) and inflammatory mediators (IL-4, IL-6, IL-10, IL-12, 1L-18, and TNF-α) were significantly upregulated in the immune system organs of clinical chickens. Taken together, these findings clarify and reveal the sequence characteristics and trends in the variation of ALV-J infection in yellow chicken flocks of South China.